ANALYSIS OF PERIODIC SERVICE MAINTENANCE 10,000 KM FOR A MITSUBISHI XPANDER - Gunawan, Reza (TRAKSI, 2024)
Mitsubishi Xpander, a 7-passenger MPV achieved success with sales of 28,307 units or 51%, including the Xpander Cross model produced by PT Mitsubishi Motors Krama Yudha Sales Indonesia (MMKSI). This success is thanks to reliable performance, ride comfort, and fuel efficiency. Despite these advantages, regular maintenance is still required to ensure optimal performance. The purpose of writing this article is to find out the periodic service maintenance process on Mitsubishi Xpander in accordance with the procedures and standards of the Mitsubishi Lautan Berlian Utama Motors Depok workshop through the case study method. Data collection was carried out by means of observation, interviews, and direct monitoring of the maintenance stages in the workshop. The maintenance process includes an initial inspection by installing a fender cover and checking the battery, checking or replacing parts including brakes, tires, engine oil, oil filters, air filters, and AC filters. The final stage is an aftercare check using a computer scanner to ensure that no sensors are damaged. Through this maintenance, various vehicle components can be checked, lubricated or replaced to prevent further damage. In addition, regular maintenance can also identify minor faults before they become major ones, which can save on long-term repair costs. So, the 10,000-kilometer maintenance is not just a routine, but an investment in your vehicle's longevity.